The Value of College Health Promotion: A Critical Population and Setting for Improving the Public's Health. Issue 4 (4th July 2017) - Lederer, Alyssa M.; Oswalt, Sara B.
ABSTRACT: College students are an important priority population, and higher education is an opportune setting for chronic disease prevention and health promotion. Yet many people do not understand why enhancing the well-being of college students is of value. In this commentary, we address 3 common misperceptions about college health promotion: (1) College students are privileged and do not reflect most of the United States population; (2) college students are generally healthy; and (3) it is not the university's responsibility to focus on students' health. We contend that in actuality, college students increasingly represent the US population; that college students struggle with numerous health concerns and are in fact unhealthier than many other subpopulations; and that institutions of higher education are a unique setting that can not only improve the health of a large segment of the US population but that doing so is actually integral to the mission of higher education. Topics that merit additional research are discussed in an effort to further enhance college health promotion practice.